MMR/c-Abl-dependent activation of ING2/p73α signaling regulates the cell death response to N-methyl-N’-nitro-N-nitrosoguanidine - Sun, Guoming (2009)
Agents inducing O(6)-methylguanine (O(6)MeG) in DNA such as N-methyl-N’-nitro-N-nitrosoguanidine (MNNG) are cytotoxic and a deficiency in mismatch repair (MMR) results in lack of sensitivity to this genotoxin (termed alkylation tolerance). Here, we show that ING2, a member of the inhibitor of growth family, is required for cell death induced by MNNG. We further observe that following MNNG treatment increases cellular protein levels of ING2 that is dependent on intact MMR function and that MNNG-induced ING2 localizes and associates with p73α in the nucleus. Suppression of ING2 by short hairpin RNA (shRNA) in MMR-proficient colorectal cancer cells decreased its sensitivity to MNNG, and in addition, abrogated MNNG-induced stabilization and acetylation of p73α. Interestingly, suppression of p73α had a greater impact on MNNG-induced cell death than ING2 leading us to conclude that ING2 regulates the cell death response, in part, through p73α. Inhibition of c-Abl by STI571 or suppression of c-Abl expression by shRNA blocked ING2 induction and p73α acetylation induced by this alkylator. Similarly, suppression of MMR (MLH1) by shRNA abrogated ING2 induction/ p73α acetylation. Taken together, these results demonstrate that MLH1/ c-Abl-dependent activation of ING2>p73α signaling regulates cell death triggered by MNNG and further suggests that dysregulation of this event may, in part, be responsible for alkylation-tolerance observed in MMR compromised cells.